Intrauterine fetal death associated socio-demographic factors and obstetric causes: a retrospective study - Mufti, Asma Hassan; Mufti, Samiya; Wani, Nasir Jeelani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The death of a fetus is emotionally traumatic for the parents. It is also distressing for the treating obstetrician. Besides being emotionally challenging, fetal demise raises a lot of questions and increases an obstetrician’s medicolegal risk. The aim of this study was to identify various maternal conditions and socio-demographic factors associated with fetal death and to find the preventable causes of fetal death. Methods: A retrospective observational study was undertaken at Lalla Ded Hospital, Srinagar, Kashmir - a tertiary care centre. The cases of singleton intrauterine fetal deaths (IUFD) with either ultrasound reports proving IUFD or diagnosed on clinical examination by absence of fetal heart sound with gestational age >28 weeks were included. Exclusion criteria includes molar pregnancy and multiple pregnancy. Results: Still birth rate in our study was 19.6 per 1000. Most of the patients with stillbirth belonged to age group of 21-30 years accounting for 67.1% of all cases. Unbooked cases comprised of 58.9%. Most of the study patients i.e. 74.7% belonged to lower middle class. In our study 39% of stillbirth cases were in the range of 28-32 gestational weeks followed by 33.6% cases in 33-37 gestational weeks. Maternal hypertensive disorders had a strong association with IUFD 33.6% (pre-eclampsia 27.4%, eclampsia 6.2%). This was followed by placental abruption comprising 11.7%. Gestational diabetes and severe anaemia accounted for 6.2% and 3.4% respectively. Gross congenital anomalies and fetal infections contributed 2.7% and 2% respectively. Conclusions: Routine antenatal checkups with identification of high risk pregnancies, better access to emergency obstetric care especially during labor, emphasis on institutional deliveries community birth attendant training should help in reducing stillbirth rates in developing countries. Optimal evaluation for future pregnancy is necessary. Counseling and support group should be involved.